2017
DOI: 10.1002/joc.5134
|View full text |Cite
|
Sign up to set email alerts
|

Onset of the Bay of Bengal summer monsoon and the seasonal timing of ENSO's decay phase

Abstract: Based on multiple sources of atmospheric and oceanic data, this study demonstrates a close relationship between the onset of the Bay of Bengal (BOB) summer monsoon (BOBSM) and the seasonal timing of El Niño-Southern Oscillation (ENSO)'s decay phase. Through distinguishing 'later-decay' and 'normal-decay' ENSO events, it is found that a later/earlier onset of the BOBSM following El Niño/La Niña is mainly caused by later-decay ENSO events, while no significant changes in BOBSM onset can be identified between nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…Notwithstanding, the negative IVT anomalies and southward wind might prevent the monsoonal circulation. Sun et al (2017) state that persistent El Niño events (warm phase) can induce later monsoon onset over the Bay of Bengal, adjacent to Bangladesh, and conversely for La Niña. A similar pattern of anomalies is observed for the positive and negative phases of ENSO during the withdrawal of the monsoon (Figures 4c,d).…”
Section: Circulation Anomalies Associated Ssta During Monsoon Onset and Withdrawal Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, the negative IVT anomalies and southward wind might prevent the monsoonal circulation. Sun et al (2017) state that persistent El Niño events (warm phase) can induce later monsoon onset over the Bay of Bengal, adjacent to Bangladesh, and conversely for La Niña. A similar pattern of anomalies is observed for the positive and negative phases of ENSO during the withdrawal of the monsoon (Figures 4c,d).…”
Section: Circulation Anomalies Associated Ssta During Monsoon Onset and Withdrawal Transitionsmentioning
confidence: 99%
“…The latter include circulation anomalies induced by intraseasonal oscillations (Karmakar and Misra, 2019), the passage of deep convection over the adjacent ocean (e.g., the Bay of Bengal) propagating into the continent, and the influence of the Tibetan plateau on circulation (Fasullo & Webster 2003;Yanai et al 1992). Furthermore, large-scale earlier or advanced monsoon onset have been associated with sea surface temperatures (SSTs) anomalies over the Indian and Pacific oceans (Lau & Yang 1997;Sun et al 2017). Likewise, El Niño (La Niña) years have been reported as associated with later (earlier) than normal onset of the monsoon season in India (Adamson & Nash 2014;Joseph et al 1994;Xavier et al 2007) and farther East (Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of the SASM shows significant interannual variability, and it is modulated by many factors. For instance, following warm El Niño-Southern Oscillation (ENSO) events (El Niño), the breakout of the summer monsoon over the South Asian regions is usually postponed, while following cold ENSO events (La Niña), the SASM onset tends to advance (Liu et al 2014b;Neena et al 2020;Sun et al 2017;Xavier et al 2007). ENSO can efficiently modulate the onset dates of the SASM through regulating the sea surface temperature (SST) anomalies in tropical oceans (Liu et al 2014b), the Walker circulation (Mao and Wu 2006;Meng and Wu 2000;Webster and Yang 1992), and the ENSOinduced 'atmospheric-bridge' (Sun et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, following warm El Niño-Southern Oscillation (ENSO) events (El Niño), the breakout of the summer monsoon over the South Asian regions is usually postponed, while following cold ENSO events (La Niña), the SASM onset tends to advance (Liu et al 2014b;Neena et al 2020;Sun et al 2017;Xavier et al 2007). ENSO can efficiently modulate the onset dates of the SASM through regulating the sea surface temperature (SST) anomalies in tropical oceans (Liu et al 2014b), the Walker circulation (Mao and Wu 2006;Meng and Wu 2000;Webster and Yang 1992), and the ENSOinduced 'atmospheric-bridge' (Sun et al 2017). Neena et al (2020) demonstrated that the El Niño in boreal spring can support two distinct eastward waveguides from the central and eastern Pacific to the SASM region, thus inducing Rossby waves to modulate the thermal structure over the SASM region in May and lead to a delayed monsoon onset.…”
Section: Introductionmentioning
confidence: 99%
“…Previous precipitation trend analyses made conclusions dependent on specific intervals (Archer and Fowler 2004;Palazzi et al 2013;Singh et al 2014) that have limited applicability to regional and global change. Moreover, synoptic-scale teleconnections with phenomena such as El Niño-Southern Oscillation (ENSO) have traditionally focused on the larger East and South Asia region (Annamalai et al 2007;Goswami and Xavier 2005;Li et al 2018;Stolbova et al 2016;Sun et al 2017;Xavier et al 2007), obscuring the vital details of its effects on SAM arrival, duration, and withdrawal in the Indus basin. The anomalous behavior of hydrometeorological characteristics due to ENSO events exhibit regional differences (Byshev et al 2012), further emphasizing the need to consider the behavior of monsoon in specific relation to the Indus basin.…”
Section: Introductionmentioning
confidence: 99%